Penerapan Nilai-nilai Pancasila dalam Kehidupan Sehari-hari Mahasiswa: Tantangan dan Solusi di Era Modern - Khalisah, Salma; Ramadlona, Oktaveralda Kayla Putri; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to identify the application of Pancasila values ​​among students in everyday life, observe the implementation of each principle, and analyze the supporting and inhibiting factors. Based on observations of 18 student respondents, it was found that tolerance, solidarity, and deliberation are values ​​that are often practiced. However, challenges such as individualism, social inequality, and lack of active participation are still major obstacles. The results of this study are expected to encourage the application of Pancasila more evenly and deeply in campus life